Investigating the relationship between religious lifestyle and social health among Muslim teachers - Ahmed, Alim Al Ayub (HTS teologiese studies, 2022)
Lifestyles are evidence for the influence of systems, cultures and civilisations within various societies. In view of that, all systems of thought aim to maintain certain ways of living in citizens to implement their ideals. Furthermore, if societies do not accept the lifestyles introduced by such systems, their intellectual foundations and values are rejected. In this regard, the Islamic lifestyle does not imply giving up all pleasures and blessings, but it takes on a divine colour to all pleasures. The objective of this study was to investigate the relationship between religious lifestyle and social health among 1000 Muslim teachers working in Kuala Lumpur, Malaysia, over a period of six months, in 2020–21. Utilising the simple random sampling method, 278 teachers were thus selected as the statistical sample and then completed some questionnaires on Islamic lifestyle and social health. Data analysis was also performed using the structural equation modeling (SEM) in the Linear Structural Relations (LISREL) statistical software package. The results demonstrated a significant positive correlation between Islamic lifestyle and social health (p = 0.58, t = 6.84).Contribution: The study results showed the importance of Islamic lifestyle in improving teachers’ social health.